The use of virtual slides in the EUROPALS examination - Bosman Fred T; van den Tweel Jan G (BMC, 2011)
Abstract Background The only realistic way to improve harmonisation of European pathology training is to define the generally accepted competencies and to test them periodically during the training programme (progress test). The European Association of Pathology Chairs and Program Directors therefore decided to implement an annual on-line test using virtual slides in addition to static jpeg images and theoretical MCQ's. The EU supported this endeavour as EUROPALS (EUROpean Pathology Assessement & Learning System). Methods To address the challenges of large scale digital testing EUROPALS teamed up with i-Path Diagnostics Ltd, a company specialising in utilisation of virtual slides in histology/pathology education and examination. Specific examination software was used in the test system. Results In the first 2 years we provided at five occasions progress tests, including 2 proctored tests, attracting hundreds of participants. The accessibility varied from suboptimal to good and improved with each subsequent test. It was influenced both by the hosting server capacity and the internet bandwidth at the user's location. Conclusion On-line testing using virtual slides is possible but requires a good collaboration between the provider and the user. Both should be aware of the requirements and threads of large scale testing with hundreds of simultaneous users.